2016
DOI: 10.1016/j.solidstatesciences.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and dielectric characterization of strontium and tantalum-based oxide and oxynitride perovskite thin films

Abstract: François Cheviré, et al.. Deposition and dielectric characterization of strontium and tantalum-based oxide and oxynitride perovskite thin films. Solid State Sciences, Elsevier, 2016Elsevier, , 54, pp.22-29. 10.1016Elsevier, /j.solidstatesciences.2015 M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT Graphical AbstractEvolution of the permittivity κ and loss tangent tanδ (@1kHz) • The permittivity of the epitaxial oxide film is 42 @1KHz• The permittivity of the oriented oxynitride film is 60 @1KHz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The sputtering targets can be either the oxynitride, the related oxide, or (for ternary oxynitrides) a single element target . Among the oxynitride thin film materials grown by reactive magnetron sputtering are LaTiO x N y , TiO x N y , Ti(Cr)O 2 :N, TaO x N y, Zn x O y N z , SiO x N y , (Sr 0.99 La 0.01 )(Ta 0.99 Ti 0.01 )O 2 N, V x ON, and Cr x ON . The obtained compositions band‐gap energies and crystalline properties of the films can be adjusted by tuning the sputtering parameters, such as the substrate temperature and the N 2 content of the reactive gas mixture .…”
Section: Thin Oxynitride Film As a Model System In Photoelectrochemicmentioning
confidence: 99%
See 3 more Smart Citations
“…The sputtering targets can be either the oxynitride, the related oxide, or (for ternary oxynitrides) a single element target . Among the oxynitride thin film materials grown by reactive magnetron sputtering are LaTiO x N y , TiO x N y , Ti(Cr)O 2 :N, TaO x N y, Zn x O y N z , SiO x N y , (Sr 0.99 La 0.01 )(Ta 0.99 Ti 0.01 )O 2 N, V x ON, and Cr x ON . The obtained compositions band‐gap energies and crystalline properties of the films can be adjusted by tuning the sputtering parameters, such as the substrate temperature and the N 2 content of the reactive gas mixture .…”
Section: Thin Oxynitride Film As a Model System In Photoelectrochemicmentioning
confidence: 99%
“…The obtained compositions band‐gap energies and crystalline properties of the films can be adjusted by tuning the sputtering parameters, such as the substrate temperature and the N 2 content of the reactive gas mixture . Relatively low substrate temperatures were used for the deposition of ternary oxynitride films, for example, TiO x N y (250–400 °C), TaO x N y (room temperature–100 °C), Zn x O y N z (150 °C), and SiO x N y (350 °C), while higher temperatures were needed for quaternary and more complex oxynitride films, for example, LaTiO x N y (800–900 °C), and (Sr 0.99 La 0.01 )(Ta 0.99 Ti 0.01 )O 2 N (750 °C) . Polycrystalline, oriented, and epitaxial films with different N contents and bandgap energies have been reported …”
Section: Thin Oxynitride Film As a Model System In Photoelectrochemicmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results of Nanamatsu [16], it is expected that the (Sr0.99La0.01)2(Ta0.99Ti0.01)2O7) oxide is ferroelectric with a Curie temperature close to room temperature. We have shown that in reactive Ar + O2 + N2 plasmas, oxide films are obtained for plasmas containing dioxygen and dinitrogen whereas oxynitride (Sr0.99La0.01)(Ta0.99Ti0.01)O2N (SLTTON) films are produced only in Ar + N2 plasmas, that is without O2 [18].…”
Section: Introductionmentioning
confidence: 99%